Analysis of pathological manifestation stemming from excess humidity in FNDE standard polysports courts in the municipality of Piripiri-PI (Research, Society and Development, 2023)
The present work aimed to survey and identify the pathologies present in FNDE (National Fund for Education Development) Standard Multisports Courts, existing in the city of Piripiri-PI. Through the visual inspection method, it was investigated the symptoms and possible causes of the manifestations observed in the buildings under study, as well as the necessary mitigating measures to solve or solve such problems. The lack of periodic maintenance of these structures is a worrisome factor, since their quality and durability are directly related to the appearance of such manifestations. Due to these and other factors, it is necessary to elaborate a project with caution and use good quality materials, always worrying about the appearance of problems arising from errors in execution, design, or indiscriminate use of available space. The present work was based on visual inspection, photographic records, and architectural designs of 03 FNDE standard multi-sports courts. From the data collected, it was found that the main pathologies observed are associated with moisture problems caused mainly by water infiltration. Among the main manifestations observed can be cited the corrosion, fissures, cracks, splits and morphing in the masonry. Periodic and specialized maintenance is essential for the conservation of buildings, as well as their conscious use.